The Rights of Children on the Move and the Budapest Declaration - Charles Oberg (MDPI AG, 2018)
It has been estimated that more than 50,000,000 children and youth have migrated across borders or been forcibly displaced within their own country. They consist of refugees, asylum seekers, internally displaced persons (IDP), economic migrants, and exploited trafficked children. They are virtually “stateless”, children deprived of the protective structures of state and family that they need and deserve and unrecognized by either their country of origin or the international community. This opinion piece starts with the personal reflections of its author on his recent work in Middle East refugee camps. It then explores the prevalence and demographics of these children and their plight. It examines the United Nation’s Convention on the Rights of the Child (CRC) and other international conventions designed to protect them. It also summarizes the International Society of Social Pediatrics and Child Health (ISSOP) Budapest Declaration on the Rights, Health and Well-Being of Children and Youth on the Move as a vehicle for improved care and vehicle for change.